PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN PELAYANAN FISKUS TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK - Anggi Sinta Dermawan; Rolyana Ferinia; Meidy Lieke Karundeng (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the impact of information technology and the quality of tax services on taxpayer compliance. Taxation challenges in Indonesia, such as the vast geographical coverage and the need for advanced technology-based administration, highlight the importance of digitalization. Digitalization is expected to enhance the efficiency of tax collection, reduce administrative costs, and simplify reporting and monitoring processes. Responsive, professional, and ethical tax services are also necessary to encourage voluntary compliance. Data were collected from 150 taxpayers in South Jakarta and analyzed using the SEM-PLS approach to evaluate the validity and relationships between variables. The results indicate that information technology does not directly influence taxpayer compliance. However, the quality of tax services plays a significant role in improving taxpayer integrity and compliance, particularly through information technology optimization. Tax digitalization supported by high-quality tax services can enhance taxpayer compliance levels and optimize tax revenue.